2005
DOI: 10.1111/j.1460-9568.2005.04508.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a cis‐acting element required for dendritic targeting of activity‐regulated cytoskeleton‐associated protein mRNA

Abstract: The mRNA encoding activity-regulated cytoskeleton-associated protein (Arc) is known to be targeted to dendritic regions that have received strong synaptic inputs. However, the cis-acting elements in Arc mRNA that mediate dendritic targeting have not been identified. To identify the dendritic targeting element (DTE) in rat Arc mRNA, we expressed reporter mRNAs containing various regions of Arc in primary hippocampal neurones and analysed their subcellular distribution by in situ hybridization. Here, we report t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 42 publications
2
56
0
Order By: Relevance
“…Examination of the sequence in this region identified an A2RE-like sequence (GCUGAGGAGGA) at position 1162 that is similar to A2RE sequences identified in ␣CaMKII and NG RNAs. Deletion of this sequence reduced dendritic targeting to 30% of injected cells, indicating that it is necessary for dendritic targeting and that the previously identified localization element in ARC RNA (Kobayashi et al, 2005) is not required for dendritic targeting in this assay. Insertion of the A2RE-like sequence from ARC RNA into GFP RNA increased dendritic targeting to 75% of injected cells, indicating that it is sufficient for dendritic targeting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examination of the sequence in this region identified an A2RE-like sequence (GCUGAGGAGGA) at position 1162 that is similar to A2RE sequences identified in ␣CaMKII and NG RNAs. Deletion of this sequence reduced dendritic targeting to 30% of injected cells, indicating that it is necessary for dendritic targeting and that the previously identified localization element in ARC RNA (Kobayashi et al, 2005) is not required for dendritic targeting in this assay. Insertion of the A2RE-like sequence from ARC RNA into GFP RNA increased dendritic targeting to 75% of injected cells, indicating that it is sufficient for dendritic targeting.…”
Section: Resultsmentioning
confidence: 99%
“…Huang et al (2003) reported that the cytoplasmic polyadenylation element (CPE) near the 3Ј end of mouse ␣CaMKII RNA is sufficient for dendritic localization of heterologous RNA in transfected neurons (Huang et al, 2003). Kobayashi identified a cis-acting element in the 3ЈUTR of ARC RNA required for dendritic localization in neurons (Kobayashi et al, 2005). Muslimov et al (2004) identified two dendritic localization elements in PKM RNA: one element at the interface between the 5ЈUTR and the open reading frame (ORF), and the other element in the 3ЈUTR.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments were performed with an Arc construct that lacked both the 5Ј-and 3Ј-UTRs. The 3Ј-UTR of Arc has previously been shown to be important in dendritic targeting, although its role in Arc protein translation is unknown (28). A plasmid encoding Arc-EYFP without the UTRs was co-expressed with ECFP in cultured neurons (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, these findings suggest that the dendritic localization of CaMKIIa mRNA depends on diverse cis-acting elements. Similarly, two different localization elements were described for the Arc mRNA (Gao et al, 2008;Kobayashi et al, 2005) but surprisingly little is known about the mechanism of Arc mRNA transport into dendrites. In hippocampal neurons the Arc transcripts are transported along dendrites in hnRNPA2-containing granules (Gao et al, 2008) and a cis-acting element on the 3 0 UTR of the Arc mRNA showed a moderate ability to target these transcripts to dendrites (Kobayashi et al, 2005).…”
Section: Cis-acting Elements and Mrna Transport Into Dendritesmentioning
confidence: 99%
“…Similarly, two different localization elements were described for the Arc mRNA (Gao et al, 2008;Kobayashi et al, 2005) but surprisingly little is known about the mechanism of Arc mRNA transport into dendrites. In hippocampal neurons the Arc transcripts are transported along dendrites in hnRNPA2-containing granules (Gao et al, 2008) and a cis-acting element on the 3 0 UTR of the Arc mRNA showed a moderate ability to target these transcripts to dendrites (Kobayashi et al, 2005). However, it is currently unknown whether hnRNPA2 is required for Arc mRNA trafficking along dendrites in vivo and the identity of the trans-acting factors that recognize the localization element present in the Arc transcripts described by Kobayashi and coworkers also remains to be determined.…”
Section: Cis-acting Elements and Mrna Transport Into Dendritesmentioning
confidence: 99%